1987
DOI: 10.1128/jvi.61.7.2182-2191.1987
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of human provirus ERV3 mRNA in human placenta: two of the three ERV3 mRNAs contain human cellular sequences

Abstract: Three polyadenylated RNAs, 9, 7.3, and 3.5 kilobases long, of a human endogenous retrovirus, ERV3, are abundant in human placental chorion, representing about 0.03 to 0.05% of the total mRNA. We characterized the structure of these mRNAs by Northern blot and S1 nuclease mapping analyses. We found that all three RNAs were spliced mRNAs that lacked 5.9 kilobases of proviral sequence, including the gag gene and most of the pol gene. In contrast to the transcription pattern usual for other retroviruses, the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(39 citation statements)
references
References 34 publications
0
37
0
2
Order By: Relevance
“…Kato et al (89) analyzed the expression of ERV-3 in placental tissues. Three polyadenylated RNAs, 9, 7.3, and 3.5 kb long, were abundant in the human placenta chorion.…”
Section: Erv-1 and Erv-3 (Herv-r): Single-copy Type Cmentioning
confidence: 99%
“…Kato et al (89) analyzed the expression of ERV-3 in placental tissues. Three polyadenylated RNAs, 9, 7.3, and 3.5 kb long, were abundant in the human placenta chorion.…”
Section: Erv-1 and Erv-3 (Herv-r): Single-copy Type Cmentioning
confidence: 99%
“…ERV-3/HERV-R is a human, single-copy ERV sequence related to MoMuLV. Kato et al (1987) have shown that in placenta ERV-3 is transcribed into three mRNA species which start 5' LTR and contain the env\ the larger two transcripts contain a human cellular gene at the 3' end. Although this ERV is abundantly expressed in normal placenta, almost complete down-regulation has been observed in choriocarcinoma cell lines (Kato et al 1988).…”
Section: Retrovirus Transregulationmentioning
confidence: 99%
“…Transcriptional levels of ERV3 and A4 1 were heterogeneous among the test subjects; some RA patients expressed high levels of each mRNA in both fresh synovial tissues and cultured synovial cells, while others expressed low or undetectable levels. Two molecular species of ERV3 mRNAs with 9 0 kb and 3 5 kb were detected in fresh synovial tissues and cultured synovial cells, but the 7-3-kb transcript could not be detected; this was reported to be a specific ERV3 mRNA in placentas [20]. Fresh synovial tissues, cultured synovial cells, and PBMC from RA patients and healthy volunteers expressed a 4 2-kb A4-1 mRNA, which was not found in placentas; hence, alternative splicing may occur in different tissues.…”
Section: Discussionmentioning
confidence: 89%